The mechanical properties and wear resistance of Hf-Ta-N coatings prepared by double glow plasma alloying technology. Issue 6 (15th March 2023) - Zang, Kai; He, Xiping; Liang, Wenping; Miao, Qiang; Sun, Yuanyuan; Yu, Haiyang; Yin, Mengjuan; Gao, Xiguang; Song, Yingdong
Abstract: Traditional metal nitrides often perform brittle fracture under heavy loads, limiting its use as wear resistant coatings. Doping a transition metal into binary nitrides can form ternary nitrides, which would have higher toughness and greater wear resistance. In this study, Hf-Ta-N coatings were prepared by double glow plasma alloying technology at different Ar/N2 ratios. The nitride content on the surface is not positively correlated with the nitrogen ratio. Under the 1:1 Ar/N2 ratio, the coating surface has the highest content of nitride. The Hf-Ta-N coatings can be divided into two parts, the outer Hf-Ta-N deposited layer and the inner Hf, Ta and Ti diffusion layer. XRD results reveal that the peaks shift due to the solid solution doping. With the rise of nitrogen flow rate, the hardness and elastic modulus increase first and then decrease, which is consistent with the nitride content on the surface. Under the 1:1 Ar/N2 ratio, the Hf-Ta-N coating prepared has the best wear resistance benefitting from its excellent mechanical property. Under the 3:1 Ar/N2 ratio, the Hf-Ta-N coating prepared was worn out during the friction test resulting from its poor mechanical property.